Hemolysis induced by an extreme mountain ultra‐marathon is not associated with a decrease in total red blood cell volume. Issue 1 (5th June 2012) - Robach, P.; Boisson, R.‐C.; Vincent, L.; Lundby, C.; Moutereau, S.; Gergelé, L.; Michel, N.; Duthil, E.; Féasson, L.; Millet, G. Y.
<x xml:space="preserve">Abstract</x> Prolonged running is known to induce hemolysis. It has been suggested that hemolysis may lead to a significant loss of red blood cells; however, its actual impact on the erythrocyte pool is unknown. Here, we test the hypothesis that prolonged running with high hemolytic potential decreases total red blood cell volume (RCV). Hemolysis (n = 22) and RCV (n = 19) were quantified in ultra‐marathon runners before and after a 166‐km long mountain ultra‐endurance marathon (RUN) with 9500 m of altitude gain/loss. Assessment of total hemoglobin mass (Hbmass) and RCV was performed using a carbon monoxide rebreathing technique. RUN induced a marked acute‐phase response and promoted hemolysis, as shown by a decrease in serum haptoglobin (P < 0.05). Elevated serum erythropoietin concentration and reticulocyte count after RUN were indicative of erythropoietic stimulation. Following RUN, runners experienced hemodilution, mediated by a large plasma volume expansion and associated with a large increase in plasma aldosterone. However, neither Hbmass nor RCV were found to be altered after RUN. Our findings indicate that mechanical/physiological stress associated with RUN promotes hemolysis but this has no impact on total erythrocyte volume. We therefore suggest that exercise 'anemia' is entirely due to plasma volume expansion and not to a concomitant decrease in RCV.